The structure and dynamics of supercooled SPC/E water confined in silica nanopores and equilibrium glassy films: a two-system study - Kuon, Nicholas J., author; Bradley, Mark R., advisor; Szamel, Grzegorz, advisor; Gelfand, Martin, committee member; Watson, Ted, committee member (Colorado State University. Libraries, 2019)
Supercooled liquids and glasses is still an area of active research. Despite the wide use of glass in society today, the underlying physics of this phase of matter still contains mysteries. This thesis will examine two different systems of supercooled liquids via molecular simulation and investigate the two systems' structure and dynamics. We first study the temperature dependence of the structure and dynamics of supercooled water confined in hydrophilic silica nanopores. In particular, we focus on the self-intermediate scattering functions. We simulate this system using the SPC/E model of water. These water molecules are confined in model MCM-41 nanopores with radii of 20, 30, and 40 Å. The structure of the water within the pores is first examined and it is found that water molecules form layers near the wall of the pores. However, in the center of the pores, the density is relatively uniform. Using this fact, the pore is divided into two regions: the core and the shell regions. The dynamics of the water molecules that start in each region are then compared. We measure the mean squared displacements and the self-intermediate scattering functions for these two regions. These measurements allows for connection with quasi-elastic neutron scattering experiments. The dependence of the self-intermediate scattering function on direction and magnitude of the wavevector is examined, as well as the function's dependence on proximity to the pore surface. In addition, the rotational-translational decoupling is measured, and it is found that the decoupling is weakly temperature dependent. The second system studied is an equilibrium glassy film deposited onto a substrate in a manner akin to vapor deposition. Glasses created in this manner can have higher kinetic stabilities and different thermodynamic properties than glasses prepared by liquid cooling. This is due to the enhanced mobility of particles at the surface of the film, which allows the particles to find lower potential energy states.Supercooled liquids and glasses is still an area of active research. Despite the wide use of glass in society today, the underlying physics of this phase of matter still contains mysteries. This thesis will examine two different systems of supercooled liquids via molecular simulation and investigate the two systems' structure and dynamics. We first study the temperature dependence of the structure and dynamics of supercooled water confined in hydrophilic silica nanopores. In particular, we focus on the self-intermediate scattering functions. We simulate this system using the SPC/E model of water. These water molecules are confined in model MCM-41 nanopores with radii of 20, 30, and 40 Å. The structure of the water within the pores is first examined and it is found that water molecules form layers near the wall of the pores. However, in the center of the pores, the density is relatively uniform. Using this fact, the pore is divided into two regions: the core and the shell regions. The dynamics of the water molecules that start in each region are then compared. We measure the mean squared displacements and the self-intermediate scattering functions for these two regions. These measurements allows for connection with quasi-elastic neutron scattering experiments. The dependence of the self-intermediate scattering function on direction and magnitude of the wavevector is examined, as well as the function's dependence on proximity to the pore surface. In addition, the rotational-translational decoupling is measured, and it is found that the decoupling is weakly temperature dependent. The second system studied is an equilibrium glassy film deposited onto a substrate in a manner akin to vapor deposition. Glasses created in this manner can have higher kinetic stabilities and different thermodynamic properties than glasses prepared by liquid cooling. This is due to the enhanced mobility of particles at the surface of the film, which allows the particles to find lower potential energy states.We study the temperature dependence of the average and single particle dynamics for particles that start at the surface of the film and for those particles that start in the bulk of the film. First, we examine the average dynamics by calculating the self-intermediate scattering functions and their relaxation times for particles that start in the surface or the bulk region. Then, we calculate the probability of the logarithm of single particle displacements for particles starting in the surface and bulk regions. We find that, in both regions, the distribution of single particle displacements indicate subpopulations of fast and slow particles. This is indicative of heterogeneous dynamics. We also find that the single particle dynamics of particles on the surface mirror particles in the bulk. However, the mirrored dynamics occur several orders of magnitude faster for particles on the surface than for those in the bulk.